2016
DOI: 10.1007/s00484-016-1198-8
|View full text |Cite
|
Sign up to set email alerts
|

Climate change: consequences on the pollination of grasses in Perugia (Central Italy). A 33-year-long study

Abstract: Many works carried out in the last decades have shown that the pollen season for taxa flowering in winter and spring, in temperate regions, has tended to be earlier, probably due to the continuous rise in temperature. The mean annual temperature in Perugia, Central Italy, was about 0.5 °C higher in the last three decades compared with that registered from 1952 to 1981. The increase of temperature took place mainly in winter and spring, while no significant variation was recorded during the summer and autumn. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…On the other hand, most of the significant results for airborne Poaceae pollen in Bavaria indicated decreases in pollen amounts, and number of days of allergenic risk (above a threshold of 30 pollen grains/m 3 ). The intensity of grass pollen seasons was governed by precipitation in spring, which is in agreement with previous work (Ghitarrini et al 2017). This weather-based behaviour of grasses could explain the negative trend in the magnitude of grass pollen seasons in Munich.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, most of the significant results for airborne Poaceae pollen in Bavaria indicated decreases in pollen amounts, and number of days of allergenic risk (above a threshold of 30 pollen grains/m 3 ). The intensity of grass pollen seasons was governed by precipitation in spring, which is in agreement with previous work (Ghitarrini et al 2017). This weather-based behaviour of grasses could explain the negative trend in the magnitude of grass pollen seasons in Munich.…”
Section: Discussionsupporting
confidence: 92%
“…Studies have shown that changes in weather conditions such as rainfall, atmospheric temperature, humidity, wind speed, and wind direction can change the seasonality and concentration of plant pollen, thus inducing allergic symptoms and leading to the occurrence and development of AR [36][37][38]. Temperature plays a very important role in increasing the pollen concentration in the air and is the main factor controlling the start of grass pollen season and the peak duration of pollen [21,39,40]. In the present study, we found that total pollen amount in Shenyang significantly correlated with daily minimum temperature, daily average precipitation, and daily average relative humidity but not with daily average temperature, maximum temperature, average atmospheric pressure, and wind scale.…”
Section: Discussionmentioning
confidence: 99%
“…Other research on the impacts of climate change on pollen season characteristics has subsequently been published in IJB, including Galán et al (2005), Frei and Gassner (2008), Newnham et al (2013) and Sofia et al (2017), to name but a few. As noteworthy as the IJB contribution to this area of research has been, it has not been the sole domain of such work.…”
Section: Aerobiology and Climate Change In Ijbmentioning
confidence: 99%